2015
DOI: 10.21776/ub.jels.2015.005.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Tapak liman (Elephantopus scaber L) Extract Induced CD4+ and CD8+ Differentiation from Hematopoietic Stem Cell/Progenitor Cell Proliferation of Mice (Mus musculus)

Abstract: Tapak liman (Elephantopus scaber L) is one of the traditional medicinal plants, which are containing several active compounds that potentially affecting hematopoietic. The aims of this study are to elucidate the effect of leaf extract of Tapak Liman on hematopoietic in mice BALB/c, by observation on relative number of cells expressing CD4/CD8, CD4/CD62L, and TER119/B220 in the spleen; TER119/B220, TER119/VLA-4 and TER119/CD34 in bone marrow, after given the leaf extract for 2 weeks. This experiment was used 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Djati et al [23] revealed that ES leaf extracts could stimulate the proliferation of the erythroid lineage (TER119 + VLA-4 + ) in the bone marrow. The increasing level of TER119 + VLA-4 + by ES alone results from a high iron (Fe) content in the ethanol extract of ES.…”
Section: Discussionmentioning
confidence: 99%
“…Djati et al [23] revealed that ES leaf extracts could stimulate the proliferation of the erythroid lineage (TER119 + VLA-4 + ) in the bone marrow. The increasing level of TER119 + VLA-4 + by ES alone results from a high iron (Fe) content in the ethanol extract of ES.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exhibited that the effects of the Elephantopus scaber at doses of 0.5 g. 1.0 g.g -1 BW could increase the CD8 T cells number, but decrease the number of CD4 and CD8 T cells at a dose of 2.0 g.g -1 BW. The lower doses could stimulate the proliferation of T cells, while at high doses, it could prevent the T cell proliferation [19].…”
Section: Analysis the Number Of Cd8+ T Cellsmentioning
confidence: 99%
“…It is due to the content of lupeol and flavonoids, which act as an antiinflammatory agent. Previous research has also shown that the effects of herbs can stimulate or otherwise suppress immunity [19,20]. The low number of CD8 + T cells in mice after administrated by E. scaber extract probably caused by the content of isodeoxyelephantopin on Tapak Liman leaves [8].…”
Section: Analysis the Number Of Cd8+ T Cellsmentioning
confidence: 99%